Curricula of Classification in the Scince of Religion - Presentation and Study - - Attia , Hoda; marhun, rahim (Islamic Sciences Journal, 2023)
The Noble Qur’an, in other than any of its verses, has established the rules for the science of comparing among religions, starting with its recognition of the existence of other religions that are sacred and null, which are the cornerstone for the emergence of this science, to its call for dialogue with the leaders of religions and its rules of dialogue and etiquette. They constitute an incentive for the Muslim mind to explore the field of compilation in this science with various approaches that simulate its motives and need. The shedding of light on Islamic schools and their impact on the science of religion in comparison with their Western counterpart is the essence of this research, especially with the voices that are exalted to give credit and preceded classification in this science for the West. This study aims to historically investigate the compilations and curricula of the two schools in the science of religions in order to refute their claums that Islamic production has entrenched in the trench of defensive the eology which has no objectivity.